Emergencies with Human Casualties and Defects In The Provision Of Medical Care In The Republic Of Kazakhstan (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The objective of the present research was to study the activities of a specialist in forensic medicine and forensic sciences in the process of eliminating the consequences of disasters associated with mass deaths of people that arose for various reasons and proceeded in different conditions. Material and Methods: In order to develop main stages of study and solve the problems, an integrated approach has been adopted with forensic-histological, chemical and biochemical, medical-forensic and biological examination subjected to analysis. Five(5) corpses, three(3) incident investigation protocols, 125 corpse identification protocols, 4 criminal cases and two documentary videos included in the research. Results and Discussion: In order to study the forensic medical examination of victims of emergencies, to solve problems and develop the main stages of the study, we used an integrated approach. There are different emergency situations such as natural catastrophes, technological incidents and terrorist acts which could lead to a great number of victims required emergency medical service including forensic autopsies. These accidents significantly affect the usual work schedule of forensic services at different levels, require additional resources and actions in order to provide the service efficiently and professionally. Conclusion: Study indicates a clear need for a thorough analysis of the causes and types of defects in the provision of medical care based on the results of medical documentation research, the development of an algorithm for analyzing the medical care provided to patients with acute abdominal surgical infection.